FIRST EXPERIENCE OF THE URETERO-URETEROANASTOMOSIS (URETEROPYELOANASTOMOSIS) IN CHILDREN WITH COMPLETE URETERAL DUPLICATION - I. M. Kagantsov; V. V. Sizonov; V. I. Dubrov; S. G. Bondarenko; N. R. Akramov; O. S. Shmyrov; G. I. Kuzovleva; R. V. Surov; A. A. Longval (Вестник урологии, 2018)
Introduction. The Duplex kidney is one of the most common anomalies of urinary system. Approaches to the surgical management of these conditions significantly differ. Taking into account the preferences of surgeons, heminephroureterectomy is offered to perform openly or laparoscopically, uretero-cysto-anastomosis of ectopic ureter or two ureters en bloc. Some publications about the possibility of ureteroureteral anastomosis have lately begun to appear. We present the experience of ureteroureteral anastomosis performed openly and laparoscopically in 9 clinics of Russia and Belarus.Objective. Improvement of treatment results of ureterohydronephrosis in children with complete ureteral duplication.Material and methods. We retrospectively reviewed medical records of 38 children who underwent ureteroureteral anastomosis surgery from 2007 to 2016. There were 10 boys (26.3%) and 28 girls (73.7%). The mean age of patients was 40.2 months. Right duplex kidney was confirmed in 15 (39.5%) children, the left one was diagnosed in 23 (60.5%) children. All the patients were divided into two groups according to the surgical technique used. Fourteen children 14 (36.8%) were included in the first group, in whom the ureteroureteral anastomosis has been performed openly, the second group comprised 24 (63.2%) patients with laparoscopically made anastomosis.Results. There weren’t any cases of conversion in this cohort. One patient in each group suffered from acute pyelonephritis. In the early postoperative period, urine leakage along the drainage occurred in 3 (12.5%) patients after laparoscopically performed ureteroureteral anastomosis, one (4.2%) child had residual ureteral stump. Thus, five (13.2%) children had complications, one (2.6%) patient required redo surgery.Conclusion. There are few clinics where ureteroureteral anastomosis is performed via open or laparoscopic approach. This operation is at the stage of development and accumulation of experience. It is a safe technique which allows to minimize the risk of loss of duplex kidney function.